SOSIALISASI LITERASI GEOTOURISM MELALUI MEDIA SOSIAL BAGI PESERTA DIDIK SMPN 1 CIMALAKA KABUPATEN SUMEDANG - Novarlia, Irena; Sukirman , Oman (LPPM Universitas Bina Bangsa, 2024)
Sumedang is currently focusing its core business on becoming a Tourism Regency. The community service program initiates the socialization of geotourism literacy by optimizing the potential of local natural tourism. The goal is to introduce the geotourism area by creating a creative marketing communication strategy through social media for promotional design that can have an impact on strengthening geotourism literacy for students at SMPN 1 Cimalaka. The program stages are divided into three stages, namely socialization, mentoring, and evaluation. Through the community development approach method, the geotourism literacy socialization program has been able to help form the character of students who better understand the potential, development and preservation of sustainable geotourism, especially in supporting the development of Sumedang as a tourism district.